Effects of Organic Peroxides on the Curing Behavior of EVA Encapsulant Resin - Kanthamas Thaworn; Piyapong Buahom; Surat Areerat (My University, 2012)
Compounds of poly(ethylene-co-vinyl acetate) (EVA with vinyl acetate content 33%) with three different organic per- oxides, namely, dialkyl peroxide, peroxyester peroxide, and peroxyketal peroxide, were prepared with a twin screws extruder and a two-roll mixing mill. The cure behavior of the EVA compounds was analyzed from rheographs, which were obtained by a moving die rheometer (MDR) at various curing temperatures between 150?C to 170?C. The effects of organic peroxides on cure behavior were examined. The dynamic curing obtained by the torque rheometer provided sufficient experimental data to show that dialkyl peroxide is not suitable because it has a high half-life temperature and its by-products can discolor the final product. Peroxyester peroxide is good for curing at temperatures in the range of 150?C to 160?C, which accomplished an ultimate cure within 5 to 8 minutes. Also, the peroxyketal peroxide has higher performance, which decreased the optimum cure time to 3 minutes. The thermal decomposition mechanism of organic peroxide was applied to explain how the cure behavior is affected by generated free radicals.
Keywords: Peroxide; Organic peroxide; Ethylene-vinyl acetate; Epoxy Resin Curing Processes